Comparison Between Dielectric Inversion Results From Synthetic Aperture Radar Co- and Quad-Polarimetric Data via a Polarimetric Two-Scale Model - Quigley, Cornelius; Brekke, Camilla; Eltoft, Torbjørn (IEEE Transactions on Geoscience and Remote Sensing, 2020)
The published version of this article is part of Cornelius Quigley's Ph.D. thesis, which is available in Munin at https://hdl.handle.net/10037/20597 In this study, we compare the retrieval results for the dielectric properties of verified oil slick, acquired using airborne multifrequency synthetic aperture radar. A polarimetric two-scale model was used to invert the radar imagery by first employing solely the co-polarization channels, and then by employing the co-polarization channels in conjunction with the cross-polarization channels, and thereby employing the full suite of polarization information available. The goal is to show that the inversion results obtained from both methods are consistent. Given that the ocean surface is a highly nondepolarizing surface scatter, the signal return within the cross-polarization channels is usually negligible and of no practical use when trying to invert the returned backscatter into useful quantities such as the dielectric constant. In this article, we employ F-SAR data, which was acquired in X-, S-, and L-bands and has an extremely low noise floor, implying that the cross-polarization ratio can be employed. A signal-to-noise analysis showed that only the L-band acquisitions were suitable for analysis in this article. The retrieval results are comparable for the two methods in the case of low dielectric values.